Initial characterization of gap phase introduction in every cell cycle of C. elegans embryogenesis - Wong, Ming-Kin; Ho, Vincy Wing Sze; Huang, Xiaotai; Chan, Lu-Yan; Xie, Dongying; Li, Runsheng; Ren, Xiaoliang; Guan, Guoye; Ma, Yiming; Hu, Boyi; Yan, Hong; Zhao, Zhongying (Frontiers in Cell and Developmental Biology, 2022)
Early embryonic cell cycles usually progress with S and M phases only without any gap phase. When the gap phases are developmentally introduced in various cell types remains poorly defined. To establish the cell-specific introduction of gap phases in embryo, we generate multiple fluorescence ubiquitin cell cycle indicators (FUCCI) in C. elegans. Time-lapse 3D imaging followed by lineal expression profiling reveals sharp and differential accumulation of the FUCCI reporters, allowing the systematic demarcation of cell cycle phases throughout embryogenesis. Accumulation of the reporters reliably identifies both G1 and G2 phases only in two embryonic cells with an extended cell cycle length, suggesting that the remaining cells divide either without a G1 phase, or with a brief G1 phase that is too short to be picked up by our reporters. In summary, we provide an initial picture of gap phase introduction in a metazoan embryo. The newly developed FUCCI reporters pave the way for further characterization of developmental control of cell cycle progression.